Preparation, Characterization, and Catalytic Property of a Cu(II) Complex with 2-Carboxybenzaldehyde-p-Toluenesulfonyl Hydrazone Ligand - Xi Shi Tai; Peng Fei Li; Li Li Liu (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Metal-organic complex hybrid materials constructed from carboxylate ligands and hydrazone ligands have exhibited potential application in many fields. In order to enrich the applications of the metai-organic complex materials, a new hydrazone ligand contains carboxylate group, 2-carboxybenzaldehyde-p-toluenesulfonyl hydrazone (L1), and its Cu(II) complex (C2), have been prepared. The structure of L1 was determined by elemental analysis, IR spectra and single crystal X-ray diffraction, and the composition of Cu(II) complex (C2) has also been determined by elemental analysis, IR and UV spectra. The catalytic activity for A3 coupling reaction of benzaldehyde, piperidine, and phenylacetylene has been investigated. The results show that Cu(II) complex displays a 100 % selectivity to the product of propargylamine during A3 coupling reaction and benzaldehyde conversions were 95.3, 94.2, and 93.4 % at 120 °C for 12 h in the first, second, and third reaction cycles, respectively.